ANALISIS KONTROL DIRI SISWA PADA KELAS X SMK NEGERI 03 PONTIANAK - Mila Pratiwi; Luhur Wicaksono; Indri Astuti (Universitas Tanjungpura, 2020)
AbstractSelf-control is very important to have so that individuals do not always behave negatively, this attitude can be embedded in students from an early age so that unwanted things do not occur within the school environment or outside the school environment. The general problem in this research is: